Distribution and determinants of urinary biomarkers of exposure to organophosphate insecticides in Puerto Rican pregnant women - Lewis, Ryan C. (Sci Total Environ, 2015)
Globally, human exposures to organophosphate (OP) insecticides may pose a significant burden to the health of mothers and their developing fetuses. Unfortunately, relevant data is limited in certain areas of the world concerning sources of exposure to OP insecticides in pregnant populations. To begin to address this gap in information for Puerto Rico, we studied repeated measures of urinary concentrations of 10 OP insecticide metabolites among 54 pregnant women from the northern karst region of the island. We also collected demographic data and self-reported information on the consumption of fruits, vegetables, and legumes in the past 48-hr before urine collection and home pest-related issues. We calculated the distributions of the urinary biomarkers and compared them to women of reproductive age from the general U.S. population. We also used statistical models accounting for correlated data to assess within-subject temporal variability of the urinary biomarkers and to identify predictors of exposure. We found that for all but two metabolites (para-nitrophenol [PNP], diethylthiophosphate [DETP]), 50(th) or 95(th) percentile urinary concentrations (the metric that was used for comparison was based on the biomarker’s detection frequency) of the other eight metabolites (3,5,6-trichloro-2-pyridinol [TCPY], 2-isopropyl-4-methyl-6-hydroxy-pyrimidine, malathion dicarboxylic acid, diethylphosphate, diethyldithiophosphate, dimethylphosphate, dimethylthiophosphate [DMTP], dimethyldithiophosphate) were somewhat lower in our cohort compared with similarly aged women from the continental United States. TCPY, PNP, DETP, and DMTP, which were the only urinary metabolites detected in greater than 50% of the samples, had poor reproducibility (intraclass correlation coefficient range: 0.19–0.28) during pregnancy. Positive predictors of OP insecticide exposure included: age; marital or employment status; consumption of cherries, grape juice, peanuts, peanut butter, or raisins; and residential application of pesticides. Further research is needed to understand what aspects of the predictors identified influence OP insecticide exposure during pregnancy.